Perlindungan Hukum Bagi Anak Berkonflik Dengan Hukum Sebagai Pelaku Pencabulan Studi Polres Bintan - Firda Usta Bella; Milla Devita Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the effectiveness of Law No. 11 of 2012 on the Juvenile Criminal Justice System in providing protection for children in conflict with the law (ABH). The law establishes various provisions related to the age limits of children, the types of penalties that can be imposed, and alternative actions as protective measures. Furthermore, this study identifies the factors that contribute to minors becoming perpetrators of sexual abuse and violence. Based on the latest systematic review, key influencing factors include family dynamics, past experiences of violence, and an unsupportive social environment. These findings indicate that effective law enforcement must consider the psychosocial aspectsof children and emphasize rehabilitative and preventive approaches in addressing ABH.